An Improved Zinc Reduction Method for Direct Determination of Nitrate in Presence of Nitrite - MIR, S.A. (Asian Journal of Chemistry, 2010)
Experimental evidence, based on zinc reduction method, has revealed that currently used metal reduction technique for determination of nitrate in presence of nitrite provides an unreliable estimate for nitrate; a) slopes over linear range for nitrite and nitrate are strikingly different such that the slope for nitrite is about 17 times steeper than that for nitrate, b) the reduction process significantly reduces nitrite (p < 0.01) and c) absorbance values for nitrite and nitrate in combination are significantly lower than the sum of absorbance values obtained by separately measuring two analytes (p < 0.01). Modified technique using urea treatment followed by metal-reduction provides more accurate and direct method for nitrate determination in presence of nitrite. Samples containing nitrate and nitrite when added urea (0.1 mL of 2 % solution) and concentrated HCl (0.2 mL) per mL sample on incubation in boiling water bath for 10 min caused complete removal of nitrite without affecting recovery of nitrate compared to untreated standard nitrate (p > 0.1). Standard urea treatment removed at least 500 μg NO2-N from the sample. Urea did not affect absorbance of NO3-N; the value for 10 μg NO3-N in presence of urea, 0.149 ± 0.002, did not differ from the value, 0.146 ± 0.002, obtained in absence of urea (p > 0.1). Nitrate recovery at 5, 8 and 10 μg NO3-N in presence of varying concentrations of nitrite, 0.5 or 50 μg NO2-N, with modified protocol has been overall 98 ± 1 per cent of basal nitrate levels.